PENELITIAN ILMIAH PENGARUH LOKASI DAN KUALITAS PELAYANAN TERHADAP LOYALITAS PELANGGAN ALFAMART GRIYA KENARI MAS - Yu Netty Nababan; Rini Wijayanti (LPPM Institut Pendidikan Nusantara Global, 2023)
This study aims to determine the effect of location and service quality on customer loyalty Alfamart Griya Kenari Mas. This type of research uses qualitative methods with descriptive analysis. Source of data used is primary data. Data collection techniques used observation, interviews, and selection, as well as data analysis techniques, data reduction, data presentation, drawing conclusions. The results of this study were that the researcher conducted interviews and had made a selection from the data that of the 20 respondents who the researchers had interviewed, there were 5 respondents who stated that they were disloyal to Alfamart Griya Kenari Mas and 15 respondents who stated that they were loyal to Alfamart Griya Kenari Mas. Results of the question regarding how customers can access Alfamart Griya Kenari Mas locations, respondents answered that they were willing to be loyal as much as 80% and not loyal as much as 20%. The results of the question regarding the Quality of Service provided by Alfamart Griya Kenari Mas to the respondent's customers answered that they were willing to be loyal as much as 90% and not good as much as 10%.